The Riskiness of Large Audit Firm Client Portfolios and Changes in Audit Liability Regimes: Evidence from the U.S. Audit Market* - CHOI, JONG‐HAG; DOOGAR, RAJIB K.; GANGULY, ANANDA R. (Contemporary Accounting Research, 2004)
We investigate whether the financial riskiness of large U.S. audit firm clienteles varied with the changing audit litigation liability environment during the period 1975‐99. Partitioning the period of study into four distinct periods (a benchmark period (1975‐84), a period of increasing concerns about litigation liability (1985‐89), a period of lobbying for reform (1990‐94), and a post‐relief period (1995‐99)), we find some evidence of risk decreases during 1985‐89, strong evidence of risk decreases during 1990‐94, and strong evidence of risk increases during 1995‐99. However, we also find that over the period of our study, a time during which Big 6 market shares grew appreciably, the proportion of litigious‐industry clients in Big 6 client portfolios grew at about the same rate as the proportion of such clients in the population. Moreover, the Big 6 share of the financially riskiest clients in the economy did not grow as fast as the overall Big 6 market share. In sum, although our evidence is consistent with the hypothesis that the riskiness of Big 6 client portfolios responded to changes in the audit litigation liability environment, we find no systematic evidence of a "race to the bottom" or "bottom fishing" by these firms in a bid to increase their market shares.